Sytuacja ekonomiczna gospodarstw rolnych podregionu szczecińskiego po przystąpieniu Polski do Unii Europejskiej - Wilczyński, Artur (Economic Situation of Farms of Szczecin Subregion after the Accession of Poland to the European Union, 2005)
The paper presents research into economic situation in Polish farms after the accession of Poland to the European Union. Results show that production returns in 2004 decreased compared with 2001 (2003 was a specific year because of drought). Net income in 2004 was diversed in analyzed farms. After the EU enlargement the income in farms which produced milk and pork increased. Crop farms had a decrease of net income (compared with 2004 and 2001) because direct payment funds only increased the production cost but no finance declined of crop producer price.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 406-410